Efeito do exercício resistido de alta intensidade sobre a sensibilidade à insulina e tolerância à glicose em ratos submetidos ao dexametasona - Rodrigues, Rejane Walessa Pequeno (2015)
Introduction: The synthetic glucocorticoids are important adjuvants in the treatment of diseases involved with the immune system and pro inflammatory diseases. Despite its importance, the indiscriminate and / or abusive use of these drugs may cause adverse effects such as iatrogenic diseases, and increased spending on public health. In this context, patients subjected to continued treatment with glucocorticoids in order to reduce the adverse effects of this drug can be used as an exercise no pharmacological strategy. Objective: To evaluate the effects of resistance exercise on blood glucose and resistance to insulin action in animals with dexamethasone. Methods: 40 males rats were used randomly into four groups: 1) Control + Sedentary (CS) 2) Control + Trained (CT) 3) Dexamethasone + Sedentary (DS) 4) Dexamentasona + Trained (DT). The training protocol was performed in squat machine (three sets, 10 reps, one-minute rest, with an intensity of 75% of one repetition maximum for four weeks). CS and CT groups received daily saline intraperitoneally whereas DT and DS groups received dexamethasone (0.2g / kg). At the end of the protocol were conducted glucose tolerance test, insulin sensitivity and maximum force test. Results: The DS and DT groups lost weight significantly following treatment with dexamethasone, CT and DT when compared groups gained strength tests of the 1st and 4th week (CT = 14.78%; DT = 36.87%) instead of CS and DS groups in the same period (p <0.05). In the glucose tolerance test, CT and DT groups showed lower area under the curve (12.99%; 22.33% respectively) compared to their respective control groups. In insulin sensitivity test, resistance exercise attenuated the action of insulin resistance induced by treatment with dexamethasone 23.81% in the DT group compared to the DS. Conclusion: Resistive Exercise was able to mitigate the deleterious effects induced by chronic use of dexamethasone on blood glucose and resistance to insulin action.